Altered Fibrin Clot Properties in Patients With Cerebral Venous Sinus Thrombosis: Association With the Risk of Recurrence. Issue 9 (September 2015) - Siudut, Jakub; Świat, Maciej; Undas, Anetta
Abstract : Background and Purpose—: Venous thromboembolism and ischemic stroke are associated with unfavorable fibrin clot structure and function. We hypothesized that denser fibrin networks displaying impaired lysability characterize patients with cerebral venous sinus thrombosis (CVST). Methods—: We assessed plasma fibrin clot properties in 50 patients (aged 38.9±9.8 years, 36 women) after the first CVST unrelated to trauma or malignancy after anticoagulation withdrawal and 50 well-matched controls. Recurrences were recorded during follow-up (18–46; median, 36 months). Results—: Clot permeability was lower in patients with CVST than in controls (Ks, 6.43±0.97 versus 7.3±1.2 10 −9 cm 2 ; P <0.001) and was associated with prolonged clot lysis time (103.0±16.8 versus 92.4±16.2 minutes; P <0.001), lower maximum rate of D-dimer release from clots (0.068 [0.064–0.071] versus 0.072 [0.067–0.078] mg/L per minute; P <0.001) and higher maximum D-dimer levels in the lysis assay (4.39±0.56 versus 4.19±0.46 mg/L, respectively; P =0.03). Patients with CVST had a slightly shorter lag phase ( P =0.02) and higher maximum absorbance of fibrin gels on turbidimetry ( P <0.001) compared with controls. Deficiencies in natural anticoagulants or antiphospholipid syndrome, and factor V Leiden occurred more often in the patients ( P <0.05). CVST recurred in 6 patients (12%) and was associated with 21% higher baseline fibrinogen ( P =0.007), 20% lower Ks ( P =0.04) and 17% greater D–Dmax ( P =0.01). Multiple logistic regression showed that only elevated D–Dmax (>4.83 mg/L) predicted CVST recurrence (odds ratio, 5.1; 95% confidence interval, 1.63–16.19) after adjustment for fibrinogen. Conclusions—: CVST is associated with the formation of more compact plasma fibrin clots and resistance to fibrinolysis, which may predispose to the recurrence. Abstract : Supplemental Digital Content is available in the text.